Enhancing Spare Part Availability Under Extreme Supply Chain Disruption: The Role of Civilian Supply Bases in Supporting UGV Systems Resilience - Karem, Oscar; Tahiri, Benet (My University, 2026)
This study examines how spare part availability for Unmanned Ground Vehicle (UGV) systems can be strengthened through the use of alternative civilian component supply bases under extreme supply chain disruption. Such disruptions may arise in contexts characterized by armed conflict, degraded infrastructure, restricted logistics access, or the loss of conventional supplier and original equipment manufacturer channels. The purpose of the study is to develop principles for resilience-oriented component sourcing that support continued system operation when established supply routes are constrained, unreliable, or unavailable. The study is based on a qualitative single-case design conducted in collaboration with a UGV startup and an established heavy vehicle manufacturer. Empirical data were collected through semi-structured interviews with eight respondents representing UGV development, heavy vehicle manufacturing, defense logistics, and operationally critical environments. The analysis followed an abductive approach, combining thematic analysis of the empirical material with theoretical insights from supply chain resilience, spare parts logistics, alternative sourcing approaches, and design for supply. The findings show that spare part availability under extreme disruption is shaped by four interrelated dimensions: operational context, component criticality, lifecycle dynamics, and organizational dependencies. Civilian heavy vehicle supply networks can strengthen resilience by providing access to standardized components, modular architectures, component reuse opportunities, and distributed aftermarket structures. However, the findings also demonstrate that civilian availability alone is insufficient. To support operational continuity, components must be physically compatible, performance-equivalent, identifiable, accessible within relevant time constraints, and possible to install using available tools and competence. The use of civilian supply bases is further limited by commercial differentiation, regulatory requirements, lifecycle mismatches, and hidden dependencies within supplier networks. Based on these findings, the study proposes four principles for resilience-oriented sourcing decisions. First, spare part needs should be evaluated at the functional level rather than solely at the component level, with priority given to functions that are critical for mission continuity. Second, civilian component availability must be converted into operational usability through operational adaptability. Third, components with broad and deep supply network commonality across platforms, applications, and aftermarket channels should be prioritized. Fourth, future availability and support continuity should be assessed alongside current availability, particularly for components exposed to obsolescence or software-related dependencies. The study contributes to supply chain resilience literature by connecting resilience theory with component-level sourcing decisions for complex technical systems operating under extreme disruption. It also provides practical guidance for organizations developing UGVs or similar platforms where civilian-military integration, alternative sourcing approaches, and long-term spare part availability are strategically important. The findings are limited by the single-case design and the absence of operational UGV deployment data. Future research should validate the proposed principles across additional cases and examine the technical, economic, and operational feasibility of specific component substitutions.
Keywords: Supply chain resilience; Spare part availability; Alternative sourcing; Civilian networks; UGV; Component criticality; Standardization; Modularity; Extreme disruption